Monitoring the effectiveness of the natural anticoagulant sulodexide in pregnant women with autoimmune hyperthyroidism on the background of hyperhomocysteinemia - A.Yu. Scherbakov; Т. А. Mіelikova (Zaporozhye State Medical University, 2017)
According to modern concepts, the occurrence of complications in utero-placental pool during pregnancy is a common cause of primary placental insufficiency, severe forms of late gestosis, recurrent miscarriage. It is obvious that the study of the nature of violations in the hemostatic system during pregnancy and the development of methods for timely correction will be the prevention of many obstetric diseases. Among the factors that affect hemostasis, thyroid hormones occupy a special place, they are able to influence not only the functional activity of platelets, but also adjust the intensity of the plasma and tissue fibrinolysis. Oppression of fibrinolytic activity is one of the pathogenetic factors of thrombosis development. The aim - to study the efficacy of natural anticoagulant sulodexide in pregnant women with autoimmune hyperthyroidism on the background of hyperhomocysteinemia. Materials and methods. The study involved 34 pregnant women with autoimmune hyperthyroidism complicated by hyperhomocysteinemia. A control group comprised 29 somatically healthy pregnant women. General clinical examination was carried out, the main indicators of all the links of the hemostatic system and the level of homocysteine were determined. Results. We determined that the main group of pregnant is characterized with chronometric and structural hypercoagulation, which manifests itself in the form of subclinical syndrome of disseminated intravascular coagulation, leading to complications of pregnancy, childbirth and the pathological condition of the fetus. Addition of anticoagulant sulodexide to the standard treatment led to the significant change in indices of all the components of hemostasis in pregnant women of the main group, in particular normalization of the total capacity of the coagulation and fibrinolytic systems. Decrease in activity of intravascular coagulation and platelet aggregation, the level of homocysteine was marked. Clinical indicators of efficacy were the elimination of the symptoms of threatened abortion, absence of reproductive loss, preeclampsia, premature placental abruption, intrauterine growth retardation, premature birth, thrombotic complications. Conclusions. The results of monitoring the effectiveness of the natural anticoagulant sulodexide show the reliable approximation of hemostasis and homocysteine levels in the intervention group to the corresponding indicators in the control group. This study determines the appropriateness of inclusion of natural anticoagulant sulodexide, which shows a good result in the normalization of blood rheology and reducing the risk of thrombotic complications, in complex therapy of pregnant women with hyperthyroidism complicated by hyperhomocysteinemia.